(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Historical records indicate that Chinese communities have consistently adapted to their surrounding environments. This adaptive capacity has influenced both activities and architectural styles found within Chinatown areas. Although the architectural forms of Chinatowns may appear similar on the surface, they often embody an integration of traditions and belief systems that shape their design. This study aims to explore, analyze, and define the relationship between the traditions and belief systems of the Chinese community and the architectural forms of Chinatown in the Lasem Chinatown area, Central Java. A qualitative approach is employed in this research to collect primary data through two main methods: (1) conducting interviews with key informants to gather data on traditions and beliefs related to activities, and (2) carrying out field observations to collect data on the architectural forms of Chinatown. The data are analyzed and interpreted to reveal the relationships between the interview information obtained and the observational findings. In the context of residential buildings, the traditions and beliefs of the Chinese community are transmitted from generation to generation without significantly altering the architectural form. Chinese architecture functions as a pragmatic replication of ancient structures from their homeland, brought by Chinese immigrants to Indonesia, particularly to Lasem. The findings of this study offer valuable insights into the relationship between traditions and belief systems and the architectural forms of Chinatown, and propose strategies for the sustainability of contemporary Chinese architectural practices.